2019
DOI: 10.15832/ankutbd.382617
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Irrigation Strategies on Yield of Drip Irrigated Sunflower Oil and Fatty Acid Composition and its Economic Returns

Abstract: A field trial was conducted to observe the effects of different irrigation strategies on the yield and the water use, oil content and marginal return of sunflower which was irrigated by means of a drip system during 2010 and 2011 under Çukurova condition of Turkey. The irrigation strategies include three irrigation intervals (A 1 : 25 mm; A 2 : 50 mm; A 3 : 75 mm of cumulative pan evaporation) and six water levels (WL) based upon the percentages of cumulative pan evaporation (WL 1 = 0.50, WL 2 = 0.75, WL 3 = 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…In the conditions of modern climatic changes, which increase the energy supply of the Polissia zone, this illuvial horizon serves as a screen for the reproduction of underground water resources, which leads to their progressive depletion. A radical means of combating such a negative ecological phenomenon for the new climatic conditions in Polissia is the destruction of this illuvial horizon by means of deep meliorative loosening or plantation plowing [14]. Such measures have been practiced in drainage reclamation to accelerate the cultivation of drained soils, which require periodic repetition to maintain a high level of homeostasis (fertility) of these soils.…”
Section: агроресурсиmentioning
confidence: 99%
See 2 more Smart Citations
“…In the conditions of modern climatic changes, which increase the energy supply of the Polissia zone, this illuvial horizon serves as a screen for the reproduction of underground water resources, which leads to their progressive depletion. A radical means of combating such a negative ecological phenomenon for the new climatic conditions in Polissia is the destruction of this illuvial horizon by means of deep meliorative loosening or plantation plowing [14]. Such measures have been practiced in drainage reclamation to accelerate the cultivation of drained soils, which require periodic repetition to maintain a high level of homeostasis (fertility) of these soils.…”
Section: агроресурсиmentioning
confidence: 99%
“…The placement of experimental sites is systematic, and replication is fourfold [14]. Tensiometric sensors installed at different depths of the soil profile and distance from the water supply point were used to determine the timing of irrigation and study evapotranspiration [10; 12].…”
Section: Relevance Of Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, studies in large containers would aid in selection of traits responsible for drought resistance. Sunflower is highly responsive to irrigation (Pejic et al, 2009; Sezen et al, 2019) [32,46] and moisture stress decreases the seed yield (Silva et al, 2015;Sezen et al, 2019) [50,45] . Furthermore, in the changing climate scenario, drought stress is likely to be continued as major abiotic limitation.…”
Section: Introductionmentioning
confidence: 99%
“…Previous papers have studied the impact of irrigation strategies and fertilization schedules on sunflower under drip irrigation in various regions. Sezen et al [17] studied the effects of different irrigation strategies on sunflower under a drip system and found that the oil contents of sunflower increased with increasing irrigation amounts. Elnaz et al [18] also found that the seed yield and oil yield of sunflower decreased by 16.2% and 22.3% when irrigation water was lacking.…”
mentioning
confidence: 99%